PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBER HEADS TOGETHER UNTUK MENINGKATKAN AKTIVITAS DAN PRESTASI BELAJAR SISWA - Bahtiar Refai (DIADIK, 2022)
The purpose of this research is to apply the number heads together (NHT) learning method to increase student activity and achievement. This research has been carried out with the Classroom Action Research (CAR) method which will be followed by a quasi experiment. The subject of this research is SD Negeri 3 Lahat which has 20 people, consisting of 10 men and 10 women. The technique of collecting data was by means of assessment sheets and tests, while data analysis was carried out using the t-test. Based on the data analysis of this study, using number heads together can increase student activity and learning achievement in mathematics learning in grade V SD Negeri 3 Lahat. The implication of the results of this study is that if teachers want to improve student achievement in social studies subjects, a number heads together type of cooperative learning model can be used